KONTRIBUSI FINTECH (FINANCIAL TECHNOLOGY) PERTANIAN DALAM MENINGKATKAN INKLUSIF KEUANGAN (Studi Analisis Pendekatan Melalui Keuangan Syariah Dengan Situs Peer to Peer Lending) - Irawan, Feri (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2023)
The purpose of this study is to examine the combination of Financial Technology (Fintech) with financial institutions, especially Islamic financial institutions because they are felt to be able to increase financial inclusion in the agricultural sector. Inclusion is a situation where people do not understand digital financial access. The emergence of problems in the first agricultural sector due to lack of land, secondly due to lack of farmer capital, and thirdly due to a lack of land cultivators has led to modernization of technology creating agro-agricultural financial technology as an alternative to increasing financial inclusion in agriculture. This type of research is qualitative research. This research outlines the extent of the role of agricultural fintech in financial inclusion in Indonesia. This study conducted 2 (two) types of research, field studies, and literature studies. Collecting data from this study through observation and non-structured interviews. The data collection method is by conducting interviews with farmers in the West Nusa Tenggara region, especially the Sumbawa Regency. The results of this study state that the use of agro-fintech in Indonesia is still lacking due to constraints such as lack of literacy in the community, inadequate human resources, inadequate legislation, and lack of network access to remote villages. Financial inclusion can increase with support from the government to improve supporting facilities and infrastructure for the use of agro fintech in Indonesia.